Probopyrinella latreuticola parasite infestation frequencies in pelagic Sargassum-associated shrimp, Latreutes fucorum. (25th November 2017) - Martin, Lindsay M; Schell, Jeffrey M; Siuda, Amy N S
Abstract: Bopyrid isopod parasitic infestation of a variety of decapod definitive hosts is common worldwide. We report frequencies of a parasite infestation in the shrimp Latreutes fucorum associated with the pelagic macroalgae Sargassum in the Gulf of Mexico, Sargasso Sea and Eastern Caribbean. Average Probopyrinella latreuticola infestation frequency was 6.7% and did not significantly vary between regions. The presence of the ectoparasite appeared to impact fertility with only one infested individual found carrying eggs. In contrast, across all three regions, 13% (of n = 4001) of the non-infested shrimp were carrying eggs. With L. fucorum accounting for three quarters of lower trophic level biomass in the pelagic Sargassum -associated faunal community, parasite infestation may have negative consequences for ecologically and commercially important populations that rely directly or indirectly on the host as a food source.